Styles of Artistic Creation in Drawings of Fifth and Sixth Grades Pupils in Al-Najaf Primary Schools (International Journal of Psychosocial Rehabilitation, 2020)
The current research consists of four chapters. The first chapter includes the research problem, which is summarized by the following question: What are the styles of the composition in the drawings of the students of the fifth and sixth primary stages in the province of Najaf? As well as the importance of research and the need and the research objective of: The aesthetics of the composition in the drawings of students in the fifth and sixth primary in the province of Najaf and identify terminology. The second chapter included two topics: The first topic: elements of the composition in the work of art The second topic: the characteristics of artistic expression in children's drawings As well as the indicators that ended the theoretical framework. The third chapter deals with the research procedures represented by the research, the research sample, the research methodology, and the analysis of five models of the outputs of the students of the fifth and sixth elementary stages in the schools of Najaf. The fourth chapter included the results of the research.